PERMAINAN HAPPY BALL UNTUK MENGEMBANGKAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA DINI - Yuliani, Dewi; Imani Khan, Rosa; Hadi Nugroho, Isfauzi (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2020)
During the early age range, children experience rapid development in various aspects. Seeing the importance of this period, appropriate stimulation efforts from the environment are needed to optimize the development of all abilities of children, including the ability to begin reading. Kindergarten children have begun to be taught to read the beginning but must be in accordance with the stages of child development, without coercion, in a fun way and should be guided by the teacher because it basically provides learning to start reading in early childhood must be with a playful atmosphere pleasant and no pressure. But in reality the process of learning to begin reading in kindergarten is still rampant using reading learning strategies that are too academic and rigid like in Elementary Schools. Therefore, researchers designed an educational game called Happy Ball that uses picture word cards. Through this Happy Ball game, it is hoped that the atmosphere of early reading learning activities for young children will be interesting and fun, the ability to read the beginning of the child is expected to be directed and develop better in a happy atmosphere. It is hoped that this game can also be used by educators to develop early reading skills in early childhood.